FEATURES OF FORMING PROFESSIONAL COMPETENCE OF STUDENTS OF MEDICAL COLLEGE: REALITIES AND PERSPECTIVES - Irina Kharashchuk (Vasyl Stefanyk Precarpathian National University, 2018)
The concept of "professional competence" is disclosed in the article, the main aspects of the process of formation of professional competence of future specialists of the medical branch are outlined; the state of this problem is analyzed at the present stage; The ways of improving the quality of students' training are determined. The author emphasizes the need to review the main ways of training a competent medical worker, emphasizes the main directions of higher education development in the countries of the European Union, outlines the guidelines for theoretical and practical work with future specialists. Key words: professionalism, competence, professional competence, mobility, self-realization.